VD_FINDINFO HC / 2016 / 922 vom 16. September 2016 - VD Tribunal cantonal (2016)
OBLIGATION D'ENTRETIEN, ENFANT, JUGEMENT DE DIVORCE, ACTION EN MODIFICATION | 134 al. 2 CC, 285 al. 1 CC, 286 al. 1 CC, 286 al. 2 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)